The Cleaning Effect of the Photocatalysis of TiO2-B＠anatase Nanowires on Biological Activity on a Titanium Surface - Gao Y (Dove Medical Press, 2020)
Yan Gao,1 Xi Lin,1 Yadong Zhao,2 Shulan Xu,1 Chunhua Lai,1 Zehong Guo,1 Wangxi Wu,1 Xianglong Ding,1 Fang Jia,1 Lei Zhou,1 Ying Liu3 1Center of Oral Implantology, Stomatological Hospital, Southern Medical University, Guangzhou 510280, People’s Republic of China; 2Department of Oral and Maxillofacial Surgery, Inner Mongolia People’ Hospital, Huhhot, Inner Mongolia 010017, People’s Republic of China; 3Department of Endodontics, Stomatological Hospital, Southern Medical University, Guangzhou 510280, People’s Republic of ChinaCorrespondence: Ying LiuDepartment of Endodontics, Stomatological Hospital, Southern Medical University, 366 South Jiang Nan Road, Hai Zhu District, Guangzhou 510280, People’s Republic of ChinaTel +86-20-84408890Fax +86-20-84433177Email 286668937@smu.edu.cnBackground: Improvements in the early osseointegration of titanium implants require investigations on the bone-implant interface, which is a critical and complex challenge. The surface cleanliness of titanium implants plays an important role at this interface. However, the implant surface would inevitably absorb contamination such as organic hydrocarbons, which is not conductive to the establishment of early osseointegration. Herein, an optimized approach for removing contamination from titanium surfaces was studied.Methods: The TiO2-B＠anatase NWs (nanowires) were prepared on titanium substrates through a hydrothermal process. A methylene blue degradation experiment was performed to assess the photodegradation activity. The cleaning effect of the photocatalysis of TiO2-B＠anatase NWs on a titanium surface and the cellular early response was determined by analyzing cell morphology, attachment, proliferation and differentiation.Results: The results indicated that the photocatalysis of TiO2-B＠anatase NWs could effectively remove hydrocarbons on titanium surfaces without sacrificing the favourable titanium surface morphology. The methylene blue degradation experiment revealed that the photocatalysis of TiO2-B＠anatase NWs had powerful degradation activity, which is attributed to the presence of strong oxidants such as ·OH. In addition, compared to the merely ultraviolet-treated titanium surfaces, the titanium surfaces treated after the NWs photocatalytic cleaning process markedly enhanced cellular early response.Conclusion: The photocatalysis of TiO2-B＠anatase NWs for the removal of contamination from titanium surfaces has the potential to enable the rapid and complete establishment of early osseointegration.Keywords: photocatalysis, nanowires, TiO2, titanium implant, osseointegration